Environmental development and its human pathways in the Holy Quran: a maqāṣidic vision: التنمية البيئية ومساراتها الإنانية في القرآن الكريم: رؤية مقاصدية - Eletrebi, Mohamed Fathy; Suleiman, Hassan; Awang, Abdul Bari; Ali Hassan, Elsayed Makki Elbishr (IIUM Press, 2020)
The Maqāsid vision is founded on the ratiocination (ta‘lÊl), public interest (maÎlaÍah) and consequence of actions (al-Ma’ālāt); and the jurisprudence of urbanism with the explanation of its related legal rulings is a priority that is important in achieving urbanization and showing its impact and role in the development of environment in the light of the objectives of Sharī‘ah, which depends on the human being with their creative abilities and capabilities, hence there comes the importance of this paper. As the research problem, the paper answers a set of questions, most notably: “what is the meaning of jurisprudence of urbanism?”, “what is its role in environmental development?”, “what is the role of maqāṣidic vision in achieving environmental urbanization?”, “what are the foundations of urbanism and what are its human pathways in the Noble Qur’an?”, “how do the objectives of Sharī‛ah draw a legislative structure that serves both people and structures?”. As the research methodology, the researchers have followed the inductive (partial), analytical and descriptive approaches. This research consists of an introduction, a preface, three subtopics, a conclusion, and a list of the most prominent sources and references. The introduction is on the importance of the topic, the reason for its choice, literature reviews, the research problem, its methodology and the proposed outlines. The first subtopic of the research is on the terminologies’ definitions; the second subtopic is about environmental development and its relationship with human beings; while the third one concerns the foundations of development in the light of the Holy Qur’ān. The study has reached several results, the most important of which are: firstly, the jurisprudence of urbanism means the legal and practical provisions regarding urbanism and building envision of the human being, as urbanization is a creative human product, and without human being there was neither urbanization nor construction. Secondly, it is necessary to develop environmental or legislative rulings that take care of the environment, in order to preserve it from the transgressions of people of authority and money on one hand, and the extremism of the ignorant people of their rights on the other hand. Thirdly, international agreements and treaties on the environment should be promoted, which are aimed to reduce pollution and preserve the environment that involve international experts and specialists with a future horizon, and local and global knowledge of environmental problems. Fourthly, environmental policies and plans beneficial to the environment should be developed by considering politics of the world and the religious guardianship as the basis for jurisprudence of politics; where cities, and dealing with the remnants of industrialization and human consumption should be planned in order to protect the environment and people, and considering that as a development priority. Lastly, the study confirms the leadership of Islamic scholars, in the past and present, in laying the foundations of environmental development through legislative and humanitarian frameworks.